Effect of thiamin (vitamin B1) on carbohydrate metabolism at rest and during exercise - Masuda, H.; Masuda, T.; Hatta, H. (The Journal of Physical Fitness and Sports Medicine, 2015)
Thiamin (vitamin B1) has often been used as a reagent to prevent fatigue. There are two possibilities concerning the anti-fatigue effect of thiamin: 1) an ergogenic effect in a non-thiamin deficient state and 2) a supplementary effect under the condition of an increasing need for thiamin due to exercise. Thiamin is a coenzyme of pyruvate dehydrogenase (PDH), which is a mitochondrial enzyme for oxidation of carbohydrate-derived substrate to generate ATP. In a thiamin deficiency, oxidation of carbohydrate is decreased due to the reduced activity of PDH. Thus a supplement of thiamin improves carbohydrate metabolism in the thiamin-deficient state. Some reports have indicated that concentrations of thiamin in tissues are decreased by exercise, i.e. the need for thiamin intake is increased. However, direct evidence supporting the hypothesis of whether or not the thiamin requirement is increased by exercise is lacking. Although it is well documented that thiamin plays an important role in the normal function of PDH reactions, whether carbohydrate metabolism is activated by supplemental thiamin during and after exercise in a normal thiamin state is unclear. This review deals with the possibility of the administration of thiamin in preventing exercise-induced fatigue by focusing on two considerations: 1) whether the need for thiamin is increased with exercise and 2) the effect of thiamin not only on carbohydrate metabolism, but also on lipid metabolism at rest and during exercise under normal dietary conditions.